Keabsahan Akta Partij Yang Ditandatangani Tidak Di Hadapan Notaris Secara Langsung Dari Konteks Cyber Notary - Maha Putra, I Made Candra; Sumardika, I Nyoman; Mahendrayana, I Made Dwi Dimas (Acta Comitas, 2025)
This study aims to examine and discuss the regulation of the making of Notarial Deeds signed not before a Notary directly and the validity of the deed in the context of cyber notary which is also described from the perspective of the Principle of tabellionis officium fideliter excercebo. This writing is a normative research, supported by several approaches, namely the legislative approach and the conceptual approach and supported by the technique of collecting legal materials using the document study technique. The results of the study of this research The making of a party deed signed not before a Notary directly has deviated from the regulations contained in Article 16 paragraph (1) letter m of the UUJN. That a notary must also be physically present, read the deed, and also sign the deed in front of the parties and witnesses. If the Notary is not present when the deed is read in front of the parties and witnesses and the deed is not signed at that time by the parties, witnesses, and notary, the deed will lose its authenticity. The validity of a party deed signed not directly before a Notary, in accordance with the provisions of Article 16 paragraph (9) UUJN, if one of the requirements as referred to in paragraph (1) letter m and paragraph (7) is not fulfilled, the Deed in question only has the power of proof as a deed under hand. The Notary must be physically present in front of the parties and also the witnesses when the deed is signed.Kata kunci : Keabsahan Akta; Akta Partij; Cyber Notary